Histoid leprosy: an uncommon variant of lepromatous leprosy - Sahi, R; Singh, A; Vaidya, R; Swamy, GG; Ahuja, JM; Chauhan, S (Journal of College of Medical Sciences-Nepal, 2012)
Histoid leprosy is an uncommon variant of lepromatous leprosy with characteristic clinical, immunologic and bacteriologic finding. Histoid leprosy can be eliminated by early diagnosis and complete treatment. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 76-78 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6733